Systematic Literature Review: 5 Years Trend in the Field of Software Engineering - Muhamad Idaham, Umar Ong; M. A., Ameedeen; Zafril Rizal, M Azmi; Imran Edzereiq, Kamarudin (American Scientific Publisher, 2018)
As a researcher, it is important to be able to focus our effort and time in contributing to new knowledge in the area that are specialize with and relevant to current research trends. It is also a main issue that is focusing our effort in the field that are growing. The objective of this paper is to identify the different fields of software engineering that are currently on the rise and areas that are falling. A methodology that involve comparison and analysis of systematical assigned keyword of papers that was published in related Q1 journals is being used to identify the current trend in the field of software engineering .Based on the result of the analysis of the IEEE Transaction in Software Engineering journal with its three systematic keyword system used, it is shown that the area of Testing (Testing and Program verification) is steadily increasing and being the preferred area of research for authors during 2012 to 2016. For future research, it is suggested that the number of journal that uses a systematical way of keyword assignment could be increase in order to strengthen the justification of current trends in the field of software engineering.